The determination of Erosion Rate on Andepts Soil Using Peanut Plants and Bench Terrace With USLE Methods and Small Plots in Kwala Bekala Estate University of North Sumatera - Rifki Iqromi Purba; Sumono Sumono; Nazif Ichwan (Universitas Sumatera Utara, 2015)
The way to prevent the broken soil (erosion) can be using vegetation methods (plants) and mechanical methods (terrace). This study was aimed to determine tolerable erosion rate and Erosion Hazard Level (TBE) the Andepts soil erosion using peanuts and bench terrace with slope of 9%, in April-July 2014 in the District Kwala Bekala using small plots and USLE predictions.The results showed that the amount of erosion using small plots for control land were 1,79 ton/(ha.year), on peanuts land were 1,18 ton/(ha.year), on bench terrace land were 0,62 ton/(ha.year) respectively with low Erosion Hasard Level (TBE) category. USLE predictions based on 10 years of rainfall data for control land were 49,34 ton/(ha.year), on peanuts land were 9,86 ton/(ha.year), on bench terrace land were 17,27 ton/(ha.year) respectively with Erosion Hazard Level (TBE) category of low to moderate. Predictions based on the USLE 4 months rainfall data for control land were 6,28 ton/(ha.year), on peanuts land were 1,25 ton/(ha.year), on bench terrace land were 2,19 ton/(ha.year) respectively with low Erosion Hazard Level (TBE) category. The amount of tolerable erosion rate is 29 tons/(ha.years). Keywords: Andepts Soil, Bench Terrace, Erosion, Peanuts